STUDENT ERROR IN CIRCUMFERENTIAL AND CIRCULAR AREA MATERIALS: ANALYSIS BASED ON THE NOLTING CLASSIFICATION - Luqman, Naufal; Fadilah, Julva Rizky; Zahra, Indry (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2025)
This study aims to analyze students' errors in solving problems around the perimeter and area of the circle based on the error category according to Nolting. These errors include conceptual, procedural, and calculation errors. The method used in this study is qualitative descriptive. The subjects of the study were 30 grade VIII students from a junior high school in Tasikmalaya. Research instruments included a written test designed to identify the type of error according to Nolting as well as a semi-structured interview to dig deeper into the causes of the error. The results showed that 28.5% of students experienced conceptual errors, 53.5% of students experienced procedural errors and 14.2% of students experienced calculation errors. Most students experience conceptual errors because they make mistakes in using the circumference and circle area formulas. Students also tend to make mistakes in distinguishing diameters and radius, as well as calculation errors on decimal numbers in multiplication and division operations. The discussion underlined that procedural errors are mostly caused by students' lack of conceptual understanding of the circle formula, while calculation errors often arise due to a lack of precision. The implementation of this research can be used by mathematics teachers to design more effective teaching strategies in overcoming students' systematic errors, such as emphasizing the understanding of basic concepts before introducing more complex problems, as well as increasing exercises that involve the application of formulas in a variety of ways.